Challenges of Securing Internet of Things Devices - Samaila, Musa Gwani (2020)
The current vision of the Internet of Things (IoT) is to ensure that everything from everywhere is connected to the Internet at all times using Internet Protocol (IP). This idea has the potential of making homes, cities, electric grids, among others, safer, more efficient, and easier to manage. Nevertheless, a number of obstacles still remain to fully realize the IoT vision, with security and privacy among the most critical. Ensuring security and privacy in the IoT is particularly complicated, especially for the resource-constrained devices due to finite energy supply and low computing power. These factors are typically at odds with most of the existing security protocols and schemes proposed for the IoT because of the intensive computational nature of the cryptographic algorithms involved. This paper performs an extensive comparison of previous surveys on the subject, and shows its novelty with respect to the previous work. It describes 9 application domains and presents, in detail, security requirements, system models, threat models along with protocols and technologies for those 9 application areas. The survey also performs an exhaustive examination of some existing mechanisms and approaches proposed in the literature for ensuring security and privacy of IoT devices. Finally, it outlines some open research issues associated with IoT security.